The struggle for history: Namibian politics of memory in the 2010s (Journal of Namibian Studies : History Politics Culture, 2022)
This paper examines the struggle for history in the Namibian political context during the 2010s. A society's public memory can be observed in many ways, in our empirical case the focus is on one memory site. We analyze this case through public newspaper discourse related to the German colonial era statue, Reiterdenkmal in Windhoek, the capital city of Namibia. The equestrian statue stood 97 years in the most prominent monumental site in the city. The relocation processes led to an emotional discourse in newspapers and delivered active discussions in terms of Namibian’s ‘correct’ history and politics of memory. The theoretical frame of this paper embraces the discourse on the use of history and memory-politics. We conclude that during the 2010s the memory politics in Namibia shifted towards nationalistic, even neo-nationalistic discourse, and sharpened the post-colonialist confrontation between citizens. Many of the opinions in the public discussions underlined the historical values and favored reconciliation, even accepting colonialist places of memory in the center of Windhoek. Nevertheless, the rider statue was banished from public view, which reveals the strengthened hegemonic role of the SWAPO party in terms of the Namibian public memory politics soon after the independence, and especially during the term of President Hifikepunye Pohamba.